2019
DOI: 10.1055/s-0040-1701144
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of Cone-Beam Computed Tomography Image: Pursuit of Perfect Orientation Plane in Three Dimensions—A Retrospective Cross-Sectional Study

Abstract: Objective This study aimed to evaluate the reproducibility of nine reference planes used in orientation of as-received cone-beam computed tomography (CBCT) images in all three dimensions. Materials and Methods The study was conducted on CBCT images of 15 adult subjects (mean age 21.2 ± 5.8 years). The anonymized CBCT images were oriented using five different methods created from nine reference planes by two experienced orthodontists. For each subject, pitch, yaw, and roll changes with five orientation methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The proposed approach offers a promising improvement in addressing the fundamental step in the clinical and research-based use of CBCT data. By providing a harmonized starting point in 3D image visualization and analysis, our approach can improve the consistency of the existing methods (e.g., orientation with horizontal and vertical planes 33 ). Additionally, for practical utilization, custom improvements can be built upon the proposed protocol toward achieving a standard harmonious workflow in the domain of craniomaxillofacial imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed approach offers a promising improvement in addressing the fundamental step in the clinical and research-based use of CBCT data. By providing a harmonized starting point in 3D image visualization and analysis, our approach can improve the consistency of the existing methods (e.g., orientation with horizontal and vertical planes 33 ). Additionally, for practical utilization, custom improvements can be built upon the proposed protocol toward achieving a standard harmonious workflow in the domain of craniomaxillofacial imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The multiplanar reconstructed images were aligned in three planes such that the axial orientation of the slices was aligned to the Frankfurt horizontal plane. The coronal orientation of the slices was aligned to the plane along the anterior margins of the right and left external acoustic meatus, and the sagittal orientation of the slices was aligned to the mid-sagittal plane as described by Balachandran et al 18 The landmarks and planes were identified and aligned by correlating the 3D reconstructions as well as multiplanar imaging.…”
Section: Methodsmentioning
confidence: 99%